2019
DOI: 10.1371/journal.pone.0221201
|View full text |Cite
|
Sign up to set email alerts
|

Pelvis and femur shape prediction using principal component analysis for body model on seat comfort assessment. Impact on the prediction of the used palpable anatomical landmarks as predictors

Abstract: A personalized pelvis and femur shape is required to build a finite element buttock thigh model when experimentally investigating seating discomfort. The present study estimates the shape of pelvis and femur using a principal component analysis (PCA) based method with a limited number of palpable anatomical landmarks (ALs) as predictors. A leave-one-out experiment was designed using 38 pelvises and femurs from a same sample of adult specimens. As expected, prediction errors decrease with the number of ALs. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Comparing to similar adult studies, this value is around 24% for the pelvis [13], and 35-45% for the femur [14], [18], [19]. Other studies in adults found 95% of the variation was found in the rst 20 (for the pelvis), 4-10 (for the femur), and 8 (for the tibia) principal components [12], [20]. Another PCA created for the tibia captured 96% of variation in the rst principal component [27].…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Comparing to similar adult studies, this value is around 24% for the pelvis [13], and 35-45% for the femur [14], [18], [19]. Other studies in adults found 95% of the variation was found in the rst 20 (for the pelvis), 4-10 (for the femur), and 8 (for the tibia) principal components [12], [20]. Another PCA created for the tibia captured 96% of variation in the rst principal component [27].…”
Section: Discussionmentioning
confidence: 64%
“…Comparing to a similar study on the adult femur, bone shape was predicted with an RMS error of 2.3mm using the same demographic and linear bone measurements, however, the best predictive factors were not determined in that study [14]. Other studies have predicted bone geometry using anatomical landmarks, nding errors in the pelvis of 4.23-5.4mm, the femur of 2.6-4.8mm, and the tibia/ bula of 2.88-3.63mm [12], [22], [30].…”
Section: Comparison To Linear Scalingmentioning
confidence: 83%
“…This transformation makes it possible to interpret the difference in shapes in the deformation metric, which is considered as being intuitive and natural. This capability of the registration algorithm allows for shape analysis, which is usually performed by using the Principal Component Analysis (PCA) [42,43,44]. Unlike the PCA, the algorithm does not require a correlation matrix, which can be large and dense (in the case of CT data).…”
Section: Discussionmentioning
confidence: 99%
“…Shape models typically use a principal component analysis (PCA) to characterise anatomical variation as a combination of weights and principal components, or modes. This approach has been used to capture the geometry of the adult pelvis 12 , 13 , femur 14 20 , the knee joint 21 , the tibia 20 , and the lower limbs collectively 22 . Using a shape model of the adult femur, for example, geometry can be predicted within 2.3 mm root mean square error using just six parameters: age, sex, height, body mass, femoral length, and epicondylar width 14 .…”
Section: Introductionmentioning
confidence: 99%